Analisis Prosedur Pemberian Pembiayaan di BMT NU Jawa Timur Cabang Asembagus Situbondo Berdasarkan Prinsip 5C dan 7P - Amir, Amir; Achmad, Achmad; Faizin, Nurul (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2023)
Financial institutions, both in the form of banks and non-banks, conventional and sharia, have a very large role in the Indonesian economy. Through its role as an intermediary institution, financial institutions become institutions that mediate between parties who have excess funds and those who lack funds. Namely by collecting funds from a surplus society, then channeling it to a deficit society in the form of financing. As a business institution that relies on trust, every financial institution must be careful in managing or maintaining any funds entrusted/entrusted to it, including the BMT NU East Java Asembagus Branch. Among them is by maximally applying the 5C principles and 7P principles in providing financing.The research data obtained consisted of primary and secondary sources. Data is collected by observation, interview, and documentation methods. The validity was tested using the triangulation method, extending participation, and persistence in observation. Data were analyzed using the Miles and Huberman method.The conclusions obtained in this study, that the provision of financing at the East Java BMT NU Asembagus Branch was carried out through several stages of activity. Starting from filling out forms, interviews, fulfilling requirements, surveys, committee meetings, and implementing financing agreements. In providing this financing, the 5C principles have been fully implemented and some of the 7P principles have been implemented.